2019
DOI: 10.1002/ppul.24439
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary functional analysis: Beating a path towards standardization

Abstract: Primary ciliary dyskinesia is an inherited disorder in which respiratory cilia are stationary, or beat in a slow or dyskinetic manner, leading to impaired mucociliary clearance and significant sinopulmonary disease. One diagnostic test is ciliary functional analysis using digital high‐speed video microscopy (DHSV), which allows real‐time analysis of complete ciliary function, comprising ciliary beat frequency (CBF) and ciliary beat pattern (CBP). However, DHSV lacks standardization. In this paper, the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 138 publications
(345 reference statements)
0
39
0
Order By: Relevance
“…Recent developments in HSVM have allowed the observation of fine movements of airway ciliary beating, the analysis of which has enabled the measurement of the functional parameters of ciliary beating, not only the CBF but also the waveform or the beating pattern, including amplitude [9][10][11]. HSVM has been shown to be an effective tool for PCD diagnosis [11,41].…”
Section: Hsvmmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent developments in HSVM have allowed the observation of fine movements of airway ciliary beating, the analysis of which has enabled the measurement of the functional parameters of ciliary beating, not only the CBF but also the waveform or the beating pattern, including amplitude [9][10][11]. HSVM has been shown to be an effective tool for PCD diagnosis [11,41].…”
Section: Hsvmmentioning
confidence: 99%
“…The functional activities of ciliary beating can be assessed by two parameters, ciliary beat frequency (CBF) and waveform [6][7][8][9][10][11][12][13][14]. Previous studies have shown that CBF is a key parameter controlling the rate of mucociliary clearance [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both ciliated HSECs in ALI culture and clinical samples collected within 30 minutes were used for cilia beating frequency (CBF) analysis. The room temperature was controlled at 25 ℃, and the humidity was maintained at 70-80%, which would not significantly affect the CBF [25]. A high-speed digital video camera (Basler AG) captured images at 100 frames per second and Sisson-Ammons Video Analysis (SAVA) software (National Instruments) was used for video analysis.…”
Section: Cilia Beating Frequencymentioning
confidence: 99%